2021
DOI: 10.15857/ksep.2021.00360
|View full text |Cite
|
Sign up to set email alerts
|

Participation in Physical Education Classes, Psychological Well-Being, and Sleep Satisfaction Among South Korean Adolescents

Abstract: PURPOSE: This study aimed to examine the associations between participation in physical education (PE) classes and the psychological well-being and sleep satisfaction of Korean adolescents.METHODS: Cross-sectional data from 127,804 Korean adolescents (aged 12–18 years) who participated in the 2016 and 2017 Korea Youth Risk Behavior Web-based Surveys (KYRBS) were analyzed. The exploratory variable was the frequency of participation in PE classes every week, while the dependent variables included the psychologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Specifically, as MVPA increases, the strength of association between SST and sleep duration weakens; one standard deviation increase in MVPA (sd = 28.83 min) was associated with approximately three minutes and twelve seconds of additionally nightly sleep when holding SST constant. Prior studies have identified associations between SST and sleep duration and their association with academic outcomes [36]; between physical education and subsequent sleep outcomes [37]; or have provided evidence from epidemiological studies pointing to regular physical activity as the most important sleep promoting behavior for the public [38]. The current study advances this literature and points to MVPA promotion as a promising strategy that may support adolescents' sleep achievement in the absence of changes to SST, despite the historical difficulty of increasing MVPA among adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, as MVPA increases, the strength of association between SST and sleep duration weakens; one standard deviation increase in MVPA (sd = 28.83 min) was associated with approximately three minutes and twelve seconds of additionally nightly sleep when holding SST constant. Prior studies have identified associations between SST and sleep duration and their association with academic outcomes [36]; between physical education and subsequent sleep outcomes [37]; or have provided evidence from epidemiological studies pointing to regular physical activity as the most important sleep promoting behavior for the public [38]. The current study advances this literature and points to MVPA promotion as a promising strategy that may support adolescents' sleep achievement in the absence of changes to SST, despite the historical difficulty of increasing MVPA among adolescents.…”
Section: Discussionmentioning
confidence: 99%